Differences in technical and tactical indicators of attacks and counterattacks in elite male karate fighters - Vidranski, T.; Maskarin, F.; Jukic, J. (Acta Kinesiologica, 2015)
In this research we identified, registered and analyzed the specific technical and tactical structures of attacks and counterattacks in karate fights in order to test our hypothesis that karate fights are primarily won by using simple techniques. In order to attain the aforementioned goals we analyzed a sample of total 274 senior contesters in 137 karate fights, who are older than 18 years and who participated in the maximum of three fights during the 2008 World Karate Championships in Tokyo. The sample was described with 48 technical and tactical indicators of situational efficiency and fight outcome variables. The data were used to form an initial matrix (48 variables in 274 fights = 4642 derived data) where events in each variable (48 technical and tactical indicators) were defined as frequencies in which an individual fighter executed a marked or unmarked technique in attack or counterattack. Such data was used to derive variables for assessment of overall situational effect of karate practitioner during the fight and for the assessment of partial situational effects of technique. The obtained results indicate that the situational efficiency and obtained differences in technical and tactical fighting concept were influenced by quick techniques of low biomechanical requirements, that is, the aforementioned techniques were used by situationally better and more effective fighters as assets of tactical surprise for gaining advantage in the attack phase. Such results confirm our hypothesis that karate fights are won by using primarily techniques with low biomechanical requirements.